An Efficient CRISPR/Cas9 Platform for Rapidly Generating Simultaneous Mutagenesis of Multiple Gene Homoeologs in Allotetraploid Oilseed Rape - Li, Chao; Hao, Mengyu; Wang, Wenxiang; Wang, Hui; Chen, Fan; Chu, Wen; Zhang, Baohong; Mei, Desheng; Cheng, Hongtao; Hu, Qiong (Frontiers in Plant Science, 2018)
With the rapid development of sequence specific nucleases (SSNs) for genome targeting , clustered regularly interspaced short palindromic repeats/CRISPR-associated protein 9 (CRISPR/Cas9) is now considered the most promising method for functional genetic researches, as well as genetic improvement in crop plants. However, the gene redundancy feature within the allotetraploid rapeseed genome is one of the major obstacles for simultaneous modification of different homologs in the first generation. In addition, large scale screening to identify mutated transgenic plants is very time-and labor-consuming using the conventional restriction enzyme-based approaches. In this study, a streamlined rapeseed CRISPR-Cas9 genome editing platform was developed through synthesizing a premade U6-26 driven sgRNA expression cassette and optimizing polyacrylamide gel electrophoresis (PAGE)-based screening approach.. In our experiment, a sgRNA was constructed to target five rapeseed SPL3 homologous gene copies, BnSPL3-A5/ BnSPL3-A4/BnSPL3-C3/BnSPL3-C4/BnSPL3-Cnn. High-throughput sequencing analysis demonstrated that the editing frequency of CRISPR/Cas9-induced mutagenesis ranged from 96.8% to 100.0% in plants with obvious heteroduplexed PAGE bands, otherwise this proportion was only 0.00%-60.8%. Consistent with those molecular analyses, Bnspl3 mutants exhibited developmental delay phenotype in the first generation. In summary, our data suggest that this set of CRISPR/Cas9 platform is qualified for rapidly generating and identifying simultaneous mutagenesis of multiple gene homologs in allotetraploid rapeseed.